A history of the Arab peoples - Hourani, Albert (Cambridge Belknap Press of Harvard University Press, 2002)
In a bestselling work of profound and lasting importance, the late Albert Hourani told the definitive history of the Arab peoples from the seventh century, when the new religion of Islam began to spread from the Arabian peninsula westwards, to the present day. It is a masterly distillation of a lifetime of scholarship and a unique insight into a perpetually troubled region.
Includes bibliographical references (p. 514-543) and indexes.
Keywords: Arab countries--History.